Pengaruh Scaffolding dalam Pembelajaran SiMaYang dalam Meningkatkan Literasi Kimia dan Metakognisi - Ummul Karimah; Sunyono Sunyono; Tasviri Efkar (Universitas Lampung, 2017)
The research was aimed to describe the effect of scaffolding strategy in SiMaYang learning to improve the chemical literacy skill and students metacognition on acid base topic. The research used Pretest-posttest Control Group Design method, which was conducted in SMA Muhammadiyah 1 Metro with Cluster Random Sampling technique.The result showed that there was 85% improvement of chemical literacy and 95% improvement of students' metacognition in experimental class which was influenced by scaffolding strategy in SiMaYang learning and 74% improvement of chemical literacy and 87% improvement of students' metacognition in the control class which was influenced by SiMaYang learning with big category on acid base topic. Based on the research, it can be concluded that scaffolding strategy has big infuence in improving the chemical literacy in the experimental class and it has moderate influence in improving metacognition skill both in the experimental class and the control class where this effect sizes measures can be distinguished by the differences of students n-gain.Penelitian ini bertujuan untuk mendeskripsikan pengaruh scaffolding pada pembelajaran SiMaYang dalam meningkatkan kemampuan literasi kimia dan metakognisi siswa pada materi asam basa. Metode yang digunakan adalah Pretest-posttest Control Group Design di SMA Muhammadiyah 1 Metro dengan teknik Cluster Random Sampling. Hasil penelitian diperoleh bahwa terdapat 85% peningkatan literasi kimia dan 95% peningkatan metakognisi siswa kelas eksperimen dipengaruhi oleh strategi scaffolding dalam pembelajaran SiMaYang dan 74% peningkatan literasi kimia dan 87% peningkatan metakognisi siswa kelas kontrol dipengaruhi oleh pembelajaran SiMaYang pada materi asam basa. Berdasarkan penelitian ini diperoleh kesimpulan bahwa strategi scaffolding berpengaruh besar dalam meningkatkan kemampuan literasi kimia pada kelas eksperimen dan berpengaruh sedang pada kelas kontrol, serta pembelajaran SiMaYang berpengaruh besar dalam meningkatkan kemampuan metakognisi pada kelas eksperimen maupun kelas kontrol yang mana besarnya effect size ini dapat dibedakan berdasarkan hasil n-gain siswa.Kata kunci: effect size, scaffolding, SiMaYang, literasi kimia, metakognisi